Modeling technological bias and factor input behavior in China's wheat production sector - Zhu, S.; Xu, X.; Ren, X.; Sun, T.; Oxley, Leslie; Rae, A.; Ma, H. (2016)
© 2015 Elsevier B.V. Over the past three decades, China has implemented reforms in the agricultural sector in an attempt to increase efficiency and food security. However, China now faces a number of environmental degradation problems, in part, caused by her past agricultural reforms. In this paper we estimate, using a provincial-based panel dataset, a third-order translog cost function for China's grain production sector over the period 1990-2011. Results from the estimation, including estimated elasticities of demand for and substitution of factors, suggest that labor and capital are substitutes. This arises because the increasing cost of labor, induced by urbanization and the growth of the manufacturing sector, has lead to a substitution of machinery for labor in the production of wheat. The results are consistent with current government policies to encourage via subsidies and agricultural mechanization, which we show to be technically, a substitute for labor. We further conclude this will create an additional bonus of reducing the amount of fertilizer that is needed to efficiently and securely produce wheat in China, as the new capital is more efficient at fertilizer distribution.